Philosophy, Science and Business Ethics: Frederick's New Normative Synthesis - Danley, John R. (Journal of business ethics, 2000)
After examining Frederick's charge in his recently published Values, Nature, and Culture in the American Corporation that philosophers and others in the field of business ethics and business and society ignore nature and technology, the paper investigates Frederick's attempt to articulate and defend a New Normative Synthesis (NNS). Since the NNS is the result of a synthesis between Frederick's theory of business values and the body of principles in business ethics, I focus on the nature of each component, the nature of the synthesis, and the nature of the resulting NNS itself. Inquiry reveals serious questions about the explanatory value of the theory of business values as a descriptive theory, as well as serious questions about the defense of the theory as normative theory. The analysis also discloses several possible interpretations of the NNS.